Synthesis And Mesomorphic Properties Of Bent-shaped 1,4-disubstituted Triazole-cored Schiff Base With Lateral Ethoxy Group - Ismail, Siti Norhazwani (2024)
Two series of bent-shaped liquid crystalline molecules, incorporating 1,4-disubstituted triazole-cored Schiff bases with lateral ethoxy groups, were successfully synthesized via the copper-catalyzed azide-alkyne cycloaddition reaction. Molecular elucidation was conducted using spectroscopic techniques, while polarizing optical microscopy (POM) and differential scanning calorimetry (DSC) were employed to investigate the optical and thermal properties of the molecules. In the first series, molecules were designed as simple bent monomers containing lateral ethoxy Schiff base with terminal flexible alkyl chains of varying lengths. Subseries A consists of cyanobiphenyl Schiff base at terminal position, exhibited stable SmA phases in compounds with longer alkyl chains, suggesting that an increase in molecular flexibility with chain lengthening favours smectogenic character. In contrast, all derivatives of subseries B with phenyl methoxy Schiff base at terminal position showed non-mesomorphic behaviour with significant overcooling tendencies. The second series, which is analogous to the first but extending into a dimer with a triazole core and an alkoxy spacer linked to a biphenyl ester on one side, displayed more distinct and pronounced mesophase characteristics. This demonstrates the significant impact of these structural modification on mesomorphic properties. All derivatives in subseries A, 8aA – 8fA exhibited nematogenic character with birefringent Schlieren texture.